Interaction of receptor-activity-modifying protein1 with tubulin - Kunz, Thomas H.; Mueller-Steiner, Sarah; Schwerdtfeger, Kerstin; Kleinert, Peter; Troxler, Heinz; Kelm, Jens M.; Ittner, Lars M.; Fischer, Jan A.; Born, Walter (Biochimica et biophysica acta, 2007)
Receptor-activity-modifying protein (RAMP) 1 is an accessory protein of the G protein-coupled calcitonin receptor-like receptor (CLR). The CLR/RAMP1 heterodimer defines a receptor for the potent vasodilatory calcitonin gene-related peptide. A wider tissue distribution of RAMP1, as compared to that of the CLR, is consistent with additional biological functions. Here, glutathione S-transferase (GST) pull-down, coimmunoprecipitation and yeast two-hybrid experiments identified β-tubulin as a novel RAMP1-interacting protein. GST pull-down experiments indicated interactions between the N- and C-terminal domains of RAMP1 and β-tubulin. Yeast two-hybrid experiments confirmed the interaction between the N-terminal region of RAMP1 and β-tubulin. Interestingly, α-tubulin was co-extracted with β-tubulin in pull-down experiments and immunoprecipitation of RAMP1 coprecipitated α- and β-tubulin. Confocal microscopy indicated colocalization of RAMP1 and tubulin predominantly in axon-like processes of neuronal differentiated human SH-SY5Y neuroblastoma cells. In conclusion, the findings point to biological roles of RAMP1 beyond its established interaction with G protein-coupled receptors.